Hey there,

Following pls find my worked solution:

<Savings>

N : (J + P + I) Total -- (1)

1 : 5 *********** 6

J : (N + P + I) Total -- (2)

1 : 4 *********** 5

P : (J + I) Total -- (3)

2 : 3 ******** 5

I - J = $72

As the savings of N, J, P and I remained constant in (1), (2), (3), we have ...

(1)x5:

N : (J + P + I) Total -- (4)

5 : 25 ********* 30

(2)x6:

J : (N + P + I) Total -- (5)

6 : 24 ********* 30

(3)x5:

P : (J + I) Total -- (3)

10 : 15 ******* 25

Hence,

N = 5u; J = 6u; P = 10u; I = 25u - P - J = 25u - 10u - 6u = 9u

Given that I - J = 72, we have ...

I - J = 72

9u - 6u = 72

3u --> 72

1u --> 24

(a)

N saved = 5u --> 5 × 24 = **$120**

(b)

P + J saved = 10u + 6u = 16u

16u --> 16 × 24 = **$384**

============

Trust this helps.

Do let me know again if this is different from your <Answerkey> or if there's further clarification.

Cheers,

Edward